Sound Art of Internet of Things Explore: Sound Sensors in the Fusion of Painting and Music - Li, Ling; Li, Yuxian (EAI Endorsed Transactions on Scalable Information Systems, 2024)
INTRODUCTION: The combination of sound art and Internet of Things (IoT) technology offers new possibilities for artistic creation. With the rapid development of the Internet of Things (IoT), sound sensors have become a powerful tool for capturing environmental sounds. This study aims to explore the application of suitable sensors in the fusion of painting and music by utilizing IoT technology to create more prosperous and interactive artworks for artists. OBJECTIVES: The study’s primary purpose is to explore the potential uses of sound sensors in art creation, especially in integrating painting and music. By deeply analyzing the interaction between sound and visual art, the researchers aim to discover new creative possibilities, thus expanding the boundaries of artistic creation. METHODS: The study utilized a comprehensive methodology that included a literature review, field research, and artistic practice. First, the literature on sound art, IoT, and art fusion was extensively reviewed to provide a theoretical foundation for the study. Second, through field research, the researchers collected practical examples of sound sensors applied in the field of art. Finally, through hands-on art creation in the artist’s studio, the researchers verified the potential applications of suitable sensors in the fusion of painting and music. RESULTS: The study found that sound sensors have many applications in painting-music fusion. By embedding suitable sensors into painting tools and music devices, artists can capture the sounds of their surroundings and transform them into visual and auditory artistic expressions. Examples from practice demonstrate how this technological innovation can bring a richer, more sensual experience to artistic creation while engaging the audience in interactive participation. CONCLUSION: The results of this study show that the combination of sound sensors and IoT technology offers new possibilities for artistic creation. By integrating proper elements in painting and music, artists can create more profound and engaging works. This innovation expands the boundaries of art and provides the audience with a more intimate and interactive experience with the artwork. In the future, further research can delve into the application of sound sensors in other artistic fields, thus promoting the integration of art and technology to move forward.